An analysis of abstracts presented to the College on Problems of Drug Dependence meeting and subsequent publication in peer review journals - Valderrama-Zurián, Juan Carlos (BioMed Central, 2009)
BACKGROUND: Subsequent publication rate of abstracts presented at meetings is seen as an indicator of the interest and quality of the meeting. We have analyzed characteristics and rate publication in peer-reviewed journals derived from oral communications and posters presented at the 1999 College on Problems of Drug Dependence (CPDD) meeting. METHODS: All 689 abstracts presented at the 1999 CPDD meeting were reviewed. In order to find the existence of publications derived from abstracts presented at that meeting, a set of bibliographical searches in the database Medline was developed in July 2006. Information was gathered concerning the abstracts, articles and journals in which they were published. RESULTS: 254 out of 689 abstracts (36.9%) gave rise to at least one publication. The oral communications had a greater likelihood of being published than did the posters (OR = 2.53, 95% CI 1.80-3.55). The average time lapse to publication of an article was 672.97 days. The number of authors per work in the subsequent publications was 4.55. The articles were published in a total of 84 journals, of which eight were indexed with the subject term Substance-Related Disorders. Psychopharmacology (37 articles, 14.5%) was the journal that published the greatest number of articles subsequent to the abstracts presented at the 1999 CPDD meeting. CONCLUSION: One out of every three abstracts presented to the 1999 CPDD meeting were later published in peer-reviewed journals indexed in Medline. The subsequent publication of the abstracts presented in the CPDD meetings should be actively encouraged, as this maximizes the dissemination of the scientific research and therefore the investment.